Gaya Komunikasi Ferdy Tahier dan Didi Riyadi dalam Tayangan Ferdy and Didi Show pada Kanal DiTivi - Khikmah Susanti; Mercy Lona Darwaty Ryndang Sriganda (Communications, 2021)
YouTube channels that have sprung up in the last 15 years, you could say these channels are owned by the general public and artists. They become YouTubers offering content that is both informative and entertainment in nature. DiTivi is a YouTube channel owned by Didi Riyadi, a well-known Indonesian artist. Didi as DiTivi's content creator creates several contents, one of which is Ferdy and Didi Show. These impressions provide informative and entertaining content. The purpose of this research is to find out how the communication style of Ferdy and Didi as hosts on the Ferdy and Didi Show shows according to the indicators, namely, language selection, word selection, pronunciation techniques and message source delivery. The method used is a qualitative descriptive approach. Data collection was obtained from the YouTube channel Ditivi broadcast by Ferdy and Didi Show by selecting two episodes to be studied based on adjustments to time and situational context. The results of this study, the communication style developed by Ferdy and Didi is an aggressive and assertive communication style. With the concept of intimate talks in the sense that the conversation takes place in a friendly and informal atmosphere, the flow of two-way communication where both of them play their role well, when they become communicators or communicants so that the feed that is thrown gets a quick response. The language selection is Indonesian with the Betawi dialect, mixed with Sundanese and English. Selection of words contains entertainment and unstructured information, the delivery of words that are inverted and repeated. Pronunciation techniques, there are differences in the way of delivery, Ferdy uses a soft and calm voice, Didi uses a morefirm and clear voice. Delivery of the source of the message, both convey based on the field of their own experiences and frames of reference for other people's thoughts.